2001
DOI: 10.1046/j.1471-4159.2001.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐dependent protein kinase phosphorylates group III metabotropic glutamate receptors and inhibits their function as presynaptic receptors

Abstract: Recent evidence suggests that the functions of presynaptic metabotropic glutamate receptors (mGluRs) are tightly regulated by protein kinases. We previously reported that cAMPdependent protein kinase (PKA) directly phosphorylates mGluR2 at a single serine residue (Ser843) on the C-terminal tail region of the receptor, and that phosphorylation of this site inhibits coupling of mGluR2 to GTP-binding proteins. This may be the mechanism by which the adenylyl cyclase activator forskolin inhibits presynaptic mGluR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 47 publications
5
71
0
Order By: Relevance
“…This 20-aa region between residues 836 and 855 corresponds to the part of the cytoplasmic domain of mGluR3 that is not conserved between mGluR3 and mGluR2. The C-terminal cytoplasmic tails of several mGluRs are phosphorylated, with both mGluR2 and mGluR3 being phosphorylated by PKA at distinct sites within the nonconserved region (20,21). We confirmed that Ser-845, situated within residues 836-855 of mGluR3, was an effective substrate for PKA in vitro.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This 20-aa region between residues 836 and 855 corresponds to the part of the cytoplasmic domain of mGluR3 that is not conserved between mGluR3 and mGluR2. The C-terminal cytoplasmic tails of several mGluRs are phosphorylated, with both mGluR2 and mGluR3 being phosphorylated by PKA at distinct sites within the nonconserved region (20,21). We confirmed that Ser-845, situated within residues 836-855 of mGluR3, was an effective substrate for PKA in vitro.…”
Section: Discussionsupporting
confidence: 61%
“…The cleaved polypeptide was efficiently phosphorylated in vitro by PKA (see also ref. 20), and mutation of Ser-845 to Ala or Asp abolished phosphorylation (data not shown).…”
Section: Identification Of Pp2c As An Mglur3-interacting Protein By Umentioning
confidence: 84%
See 1 more Smart Citation
“…Group III mGluRs are known to inhibit G-protein-mediated increase in intracellular cAMP and adenylyl cyclase (Con and Pin 1997). This mechanism was shown to mediate a presynaptic inhibition of glutamate release by group III mGluRs (Cai et al 2001). We suspect a similar action in the postsynaptic sites of neocortical inhibitory circuits that has not yet been reported.…”
Section: Discussionmentioning
confidence: 64%
“…However, a1 ARs could exist anywhere at the synapse in BNST, including being present at multiple locations, allowing for other mechanisms of mGluR8 disruption by a1 ARs. Alternatively, in the hippocampus, presynaptic group III mGluRs, including mGluR8 specifically, can be inhibited through phosphorylation by PKA (Cai et al, 2001). Thus, any receptor feeding into the cAMP/PKA pathway could desensitize mGluR8.…”
Section: Discussionmentioning
confidence: 99%